The Biology of the porifera (Published for the Zoological Society of London by Academic Press, 1970)
This methods of selections has brought together conflicting points of view on several topics, notably on phylogeny, cell adhesion, and other aspects of morphogenesis and clearly dinies the volume the right to be regarded as a treatise on sponges.